Characterization and In Vivo Antiangiogenic Activity Evaluation of Morin-Based Cyclodextrin Inclusion Complexes - Federica De Gaetano; Fatima Margani; Vincenzina Barbera; Valeria D'Angelo; Maria Paola Germanò; Venerando Pistarà; Cinzia Anna Ventura (MDPI AG, 2023)
Morin (MRN) is a natural compound with antiangiogenic, antioxidant, anti-inflammatory, and anticancer activity. However, it shows a very low water solubility (28 μg/mL) that reduces its oral absorption, making bioavailability low and unpredictable. To improve MRN solubility and positively affect its biological activity, particularly its antiangiogenic activity, in this work, we prepared the inclusion complexes of MNR with sulfobutylether-β-cyclodextrin (SBE-β-CD) and hydroxypropyl-β-cyclodextrin (HP-β-CD). The inclusion complexes obtained by the freeze-drying method were extensively characterized in solution (phase-solubility studies, UV-Vis titration, and NMR spectroscopy) and in the solid state (TGA, DSC, and WAXD analysis). The complexation significantly increased the water solubility by about 100 times for MRN/HP-β-CD and 115 times for MRN/SBE-β-CD. Furthermore, quantitative dissolution of the complexes was observed within 60 min, whilst 1% of the free drug dissolved in the same experimental time. 1H NMR and UV-Vis titration studies demonstrated both CDs well include the benzoyl moiety of the drug. Additionally, SBE-β-CD could interact with the cinnamoyl moiety of MRN too. The complexes are stable in solution, showing a high value of association constant, that is, 3380 M−1 for MRN/HP-β-CD and 2870 M−1 for MRN/SBE-β-CD. In vivo biological studies on chick embryo chorioallantoic membrane (CAM) and zebrafish embryo models demonstrated the high biocompatibility of the inclusion complexes and the effective increase in antiangiogenic activity of complexed MRN with respect to the free drug.